The Involvement of Father's Role in Parenting to Form Leadership Attitude in Early Age Children - Rahmatika, Apriyana Kurnia; Sugiyo Pranoto, Yuli Kurniawati (BELIA: Early Childhood Education Papers, 2020)
This study aims to describe the involvement of father’s role in parenting to form leadership attitudes of children in early childhood in naval army housing complex Kalibanteng Kidul in the city of Semarang. This research is a qualitative descriptive study which uses data collection methods of observation, interviews, and document analysis. The data analysis technique used is the theory of Miles and Huberman. The results of the study explain the involvement of the father's role in parenting can form leadership attitudes such as: self-confidence, honesty, courage, and assertiveness. In addition to the involvement of father who forms leadership attitudes, school environment also facilitates children with activities to optimize their leadership attitudes, such as a sense of leading, responsibility, patience, and competency. There are also supporting factors such as: children’s surrounding environment/the military family, father’s profession that becomes model of a leader figure, father-children interaction, military family parenting, parent’s support and school environment, school activities that form attitudes that can be the nature of a leader, and children’s self-motivation to want to be a leader. On the contrary, there are also several inhibiting factors as follows: the limited amount of father's time due to his work, parenting is done more by the mother, parents who do not prioritize discipline and independence in parenting, and the lack of parental awareness of the building leadership attitudes. The conclusion of this study is the involvement of father’s role is very important for the formation of children’s leadership attitudes and there are other factors in supporting the optimization of the formation of leadership attitudes such as school and surrounding environment. This research is important and it becomes an issue for the involvement of father’s role in daily parenting.